Ethnomedicinal Potential of indigenous plants of the Northern Balochistan, Pakistan - Ullah, Rafiq; Ahmed, Nadeem; Jelani, Ghulam; Khan, Muhammad Nauman; Kaplan, Alevcan; Wahab, Sana (Ethnobotany Research and Applications, 2024)
Background: The Pakistani region of Balochistan lies within the borders of three countries (Pakistan, Iran, Afghanistan) and is a large, arid and mountainous province that makes up a large part of the country's land area. It is called a sacred land by the locals as it has different ecological conditions such as attractive landscapes, magnificent forests and a variety of unique flora and fauna. This study, the medicinal use of plants in the Northern region of Balochistan province in Pakistan was documented. Methods: During the field research conducted in 2021-2023, an open-ended survey was prepared to record and document the ethnomedicinal use of high-value medicinal plants in the study area. The ethnomedicinal data was collected by administering the prepared questionnaire to local people, pansars, judges, local midwives and old wise men (both men and women). Results: A total of 93 ethomedicinally important plant species from 40 families are reported from the northern Balochistan. Out of the 93 species, 1 species (1.07 %) was a gymnosperm, 11 species (11.82 %) belonging to 6 families were monocotyledons and the remaining 81 species (87.09 %) belonging to 33 families were of dicotyledons. Papilionaceae was the leading family in terms of species diversity, represented by 14 medicinal plant species (15.05 %) belonging to 9 genera (9.67 %), followed by Asteraceae with 9 species (9.67 %) belonging to 9 genera (9.67 %), Apiaceae with 7 species (7.52 %) belonging to 7 genera (7.52 %), Brassicaceae with 5 species (5.37 %) belonging to 5 genera (5.37 %) and Lamiaceae with 5 species (5.37 %) belonging to 4 genera (4.30 %). The remaining 36 families had less than 5 species each (5.37 %). According to habit, most medicinal plants were herbs with 55 species (59 %), followed by shrubby plants with 33 species (36 %) and trees were represented by 5 species (5 %). The most common and important plant part used in the preparation of recipe was the whole plant, 37 species (39.78 %), followed by leaves, 14 species (15.05 %) and seeds, 10 species (10.75 %). Oral ingestion was the main route of administration with 74 (79%) species, followed by topical application with 9 species (10 %), while 10 species (11 %) were used both topically and orally. The ethnomedicinal study revealed a total of ninety-three species most important for therapeutic use. The bulb of Allium griffithianum is used orally for mouth ulcers, while the whole plant of Achyranthes aspera is used for coughs and rheumatism. Therefore, some species are also used for multiple purposes (Berberis baluchistanica, Onosma hispida, Citrullus colocynthis, Ephedra intermedia, Acacia nilotica, Astragalus khalifatensis, Berchemia pakistanica, Ziziphus mauritiana and Withania coagulans), while only a few plants in this area have a single therapeutic use (Achillea wilhelmsii, Iphiona grantioides, Matricaria aurea, Microcephala lamellate, Heliotropium baluchistanicum, Cardaria chalepense, Sisymbrium irio, Tetracme stocksii, Acanthophyllum grandiflorum, Convolvulus spinosus, Cuscuta pulchella, Euphorbia granulata, Ricinus communis, Iris stocksii, Alhagi maurorum, Caragana brachyantha, Parkinsonia aculeata, Papaver pavoninum, Sorghum halepense, and Ranunculus falcatusi). Conclusions: Since the species have medicinal value, the results of our study provide important scientific as well as practical insights. In this context, we believe that the species used by local people in traditional treatment will be important for the protection of social health. Keywords: Ethnomedicinal plants; Herbal recipes; Northern Balochistan; Pakistan